Selective solid phase extraction and pre-concentration of Cu(II) ions from aqueous solution using Cu(II)-ion imprinted polymeric beads. Issue 2 (April 2020) - Mishra, Shraddha; Tripathi, Amit
Abstract: A new Cu(II)-ion imprinted polymeric (IIP) beads (∼ 450 μm) were prepared by suspension polymerization of methyl methacrylate (monomer) and ethylene glycol dimethacrylate (crosslinker) in the presence of Cu(II)-picolinic acid (functional ligand) binary complex wherein Cu(II) ion is used as an imprint ion. The imprinted Cu(II) ions were removed from the polymeric matrix using 1 M HCl, thereby creating the cavities for the selective adsorption of Cu(II) ions. For the comparison purpose, control polymeric (CP) beads were similarly prepared without the use of Cu(II) ions. The prepared IIP beads were characterized using different analytical techniques such as scanning electron microscopy, energy dispersive X-ray spectroscopy, fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, surface area and pore size distribution. The optimum solution pH was determined to be 5.0 and equilibrium was achieved within 60 min. Nature of eluent, eluent concentration and sample volume were also studied. The synthesized IIP exhibited high selectivity coefficients for the Cu(II)/Ni(II), Cu(II)/Co(II) and Cu(II)/Zn(II) are 26.8, 34.0 and 57.7, respectively. The IIP beads can be used up to seven adsorption/desorption cycles with the recovery not less than 97 %. The detection limit corresponding to three times the standard deviation of the blank was found to be 0.3 μg mL −1 .